PERSEPSI LEMBAGA SWADAYA MASYARAKAT TERHADAP PELAKSANAAN, PENERTIBAN DAN PEMBINAAN GELANDANGAN DAN PENGEMIS OLEH DINAS SOSIAL DAN PEMAKAMAN KOTA PEKANBARU - Vika Nurmalasari; Hambali '; Zahirman ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This research is motivated by the proliferation of homeless and beggars in the city of Pekanbaru which mosey and begging in public places. Formulation of the problem in this research is how the perception of non goverment organizations on the implementation, enforcement and development of homeless and beggars by the social services and the funeral of Pekanbaru. The purpose of this study was to determine the perception of non goverment organizations on the implementation, enforcement and development of homeless and beggars by the social services and the funeral of Pekanbaru. The study population was as many as 30 non goverment organizations working in the social field, and the sample 6 non goverment organizations by using purposive sampling technique. Instrument data research is a questionnaire with 36 questions. Data analysis using descriptive and qualitative analysis. Research in the field indicates that respondents non goverment organizations officers who answered "very good" in the amount of 0.94% who answered "good" that is equal to 37.04% who answered "less good" by 55.09% who answered "not good" that is equal to 6.94%. So we can conclude the perception of non goverment organizations to conduct, control and guidance homeless and beggars by the social services and the city cemetery is less well Pekanbaru.Keywords: Perception of non Government Organization, policing and coaching, vagrants and beggars2